Improved bacterial nanocellulose production from glucose without the loss of quality by evaluating thirteen agitator configurations at low speed. Issue 6 (10th September 2019) - Chen, Genqiang; Chen, Lin; Wang, Wei; Chen, Shiyan; Wang, Huaping; Wei, Yen; Hong, Feng F.
Summary: Thirteen agitator configurations were investigated at low speed in stirred‐tank reactors (STRs) to determine if improved crude bacterial nanocellulose (BNC) productivity can be achieved from glucose‐based media while maintaining high BNC quality using Komagataeibacter xylinus ATCC 23770 as a model organism. A comparison of five single impellers showed the pitched blade (large) was the optimal impeller at 300 rpm. The BNC production was further increased by maintaining the pH at 5.0. Among the single helical ribbon and frame impellers and the combined impellers, the twin pitched blade provided the best results. The combined impellers at 150 rpm performed better than the single impellers, and after optimizing the agitation conditions, the twin pitched blade (large) and helical ribbon impellers performed the best at 100 rpm. The performances of different agitators at low speed during BNC production were related to how efficiently the agitators improved the oxygen mass transfer coefficient. The twin pitched blade (large) was verified as providing the optimum performance by an observed crude BNC production of 1.97 g (L×d) −1 and a BNC crude yield of consumed glucose of 0.41 g g −1, which were 2.25 and 2.37 times higher than the initial values observed using the single impeller respectively. Further characterization indicated that the BNC obtained at 100 rpm from the STR equipped with the optimal agitator maintained high degree of polymerization and crystallinity. Abstract : Thirteen agitator configurations were investigated at low speed in stirred‐tank reactors (STRs) to determine if improved crude bacterial nanocellulose (BNC) productivity can be achieved from glucose‐based media while maintaining high BNC quality using Komagataeibacter xylinus ATCC 23770 as a model organism. Among the single helical ribbon and frame impellers and the combined impellers, the twin pitched blade provided the best results. Further characterization indicated that the BNC obtained at 100 rpm from the STR equipped with the optimal agitator maintained high degree of polymerization and crystallinity.